Neuropsychological reactions to vertical and horizontal video content in consumer behavior: a theoretical and economic analysis - Tytarenko, Yana (Актуальні питання економічних наук, 2025)
The article examines the neuropsychological mechanisms of perception of vertical and horizontal video content in the context of consumer behavior. It is substantiated that the spatial-visual orientation of the video determines the nature of emotional involvement, the level of cognitive load and subsequent behavioral reactions of consumers. The purpose of the study is to theoretically substantiate the influence of the visual orientation of video content on the emotional-cognitive processes of the consumer and to develop an author’s model that explains the relationship between neuropsychological reactions and the economic effectiveness of marketing communication. The methodological basis is the methods of systemic, structural-functional and cognitive analysis, which made it possible to generalize scientific approaches to the study of neuromarketing, the economics of attention and the theory of cognitive load. Based on analytical modeling, the author’s concept «Model of Three Focuses» is proposed, within which three interrelated levels of perception are distinguished: visual, emotional and cognitive-behavioral. Results. It has been established that vertical videos activate the limbic system, causing rapid emotionally colored reactions, effective for impulsive decisions and short-term communications; on the other hand, horizontal formats stimulate the prefrontal areas of the brain, enhancing analytical perception, trust and loyalty of consumers. Conclusions. The developed model proves that neuropsychological reactions directly affect the economic efficiency of video marketing, establishing a connection between psychological processes of attention and financial results of the business. The practical significance of the study lies in the possibility of using the model to predict behavioral reactions, assess the effectiveness of communication strategies and form long-term brand trust capital. The results of the study expand the theoretical basis of the neuroeconomic approach to video marketing and open up prospects for further empirical measurements in the field of digital communications and behavioral analytics.